Cover Picture: Disorder Engineering in Monolayer Nanosheets Enabling Photothermic Catalysis for Full Solar Spectrum (250–2500 nm) Harvesting (Angew. Chem. Int. Ed. 10/2019). Issue 10 (4th February 2019) - Yang, Min‐Quan; Shen, Lei; Lu, Yuyao; Chee, See Wee; Lu, Xin; Chi, Xiao; Chen, Zhihui; Xu, Qing‐Hua; Mirsaidov, Utkur; Ho, Ghim Wei
Abstract : Maximizing light harvesting while sustaining high photoredox capability is crucial for realizing high photocatalytic solar‐to‐chemical conversion. In their Communication onpage 3077, G. W. Ho and co‐workers report an order–disorder D‐HNb3 O8 monolayer structure to perform two disparate functions of photoexcitation to generate charge carriers and solar heating to thermally boost reaction kinetics. This solar thermal‐mediated photocatalyst system fulfills full solar energy utilization from 250 to 2500 nm.